Academic Dishonesty and Locus of Control in Public and Private Universities: A Comparative Study - Azam, Sumbul; Abbas, Hira; Tariq, Maryam (Annals of Human and Social Sciences, 2024)
The purpose of the study is to analyze relationship between academic dishonesty and locus of control in public and private universities. The research regarding academic dishonesty and locus of control in Pakistan is not well conducted, so there is an essential need to examine the correlation between these variables. Through purposive sampling technique (N=189) students age ranged between 18-25 years were selected from universities of Karachi. Rotter’s Internal-External Locus of Control Scale (Rotter, 1966) and Academic Dishonesty Scale (Bashir & Bala, 2018) were used to measure the research variables. The results revealed that there is weak positive correlation between these two variables (r=0.38, p<0.05). The findings of research highlighted that there would be a difference between academic dishonesty in public and private university students. Results of our research indicate that academic dishonesty is prevalent in both public and private universities. This study is indicating how grave matter of academic dishonesty is and universities should take measures to ensure that culture of learning should prevail instead of grades.